Perceived barriers/facilitators to a healthy lifestyle among diverse adolescents with overweight/obesity: A qualitative study. (18th August 2020) - Cardel, Michelle I.; Szurek, Sarah M.; Dillard, Jackson R.; Dilip, Abhya; Miller, Darci R.; Theis, Ryan; Bernier, Angelina; Thompson, Lindsay A.; Dulin, A.; Janicke, David M.; Lee, Alex M.
Summary: Objective: Effectiveness of behavioural obesity treatments in adolescents is modest. Thus, incorporating participant feedback may lead to improvement of intervention acceptability. This qualitative study's objective was to assess perceived barriers/facilitators to weight loss and healthy lifestyles among diverse adolescents with overweight/obesity (OW/OB). Methods: Adolescents ages 14–19 with BMI ≥ 85th percentile participated in focus groups and identified perceived barriers/facilitators to weight loss and healthy lifestyles. Results: Ten sex‐stratified focus groups ( n = 41; n = 13 males, n = 28 females) were conducted in 2018 and 2019. Females reported experiencing weight struggles, whereas males often stated no struggles with weight, despite all participants meeting criterion for OW/OB. Barriers included eating behaviours, family members and internal motivation, with additional barriers of physical activity, friends, time and support cited in females. Facilitators included parental, familial and peer support of healthy eating and exercise, modelling behaviours, internal motivation and organized sports. Two additional findings regarding adolescents' perceived barriers/facilitators include substantial overlap and sex differences of perceived barriers/facilitators. Conclusions: Adolescent males and females with OW/OB experience weight status differently, affecting their perceived barriers/facilitators to weight loss and healthy lifestyles. Tailoring weight management interventions to the unique needs of adolescent females versus adolescent males has the potential to improve intervention quality and effectiveness.